Learning Constraints in Early Childhood Education: A Descriptive Qualitative Study of Inadequate Facilities and Infrastructure at PAUD Ikhlas Sei Kera Hilir 1 - Sonia Septiani Sembiring; Helda Emeninta Bangun; Jese Karona Saragih; Lovian Malona Manulang (Era Scientific Publisher, 2026)
Early Childhood Education plays a crucial role in shaping children’s character, moral values, and foundational abilities. However, PAUD ikhlas Sei Kera Hilir 1 continues to face limitations in learning facilities and infrastructure, which affect the effectiveness of the learning process. This study aims to analyze the impact of inadequate facilities on children’s learning experiences and to explore the roles of parents and the government in supporting the improvement of early childhood education quality. This research employed a descriptive qualitative approach involving five informants: two early childhood teachers as primary informants, two parents, and one village administrative officer as supporting informants. Data were collected through observation, in-depth interviews, and documentation. Data analysis followed the interactive model proposed by Miles and Huberman (1994), consisting of data reduction, data display, and conclusion drawing. Content analysis and thematic coding were also applied, and data trustworthiness was ensured through source and methodological triangulation. The findings reveal that limited classroom space, a lack of educational play materials, and a narrow learning environment negatively affect children’s motivation to learn. Parental support remains limited due to economic constraints, while government assistance is primarily focused on children’s nutrition and health rather than educational facilities. In conclusion, inadequate learning facilities and infrastructure hinder the learning process at PAUD IKHLAS Sei Kera Hilir 1, highlighting the need for collaborative efforts among teachers, parents, and the government to improve the quality of learning facilities in early childhood education.